Dr. Hardik Doshi — Deep Plane Facelift — Long Island - Doshi, Hardik (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Hardik Doshi, practicing in Long Island, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002989; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; long island